KORELASI PEMAHAMAN NAHWU TERHADAP KEMAMPUAN INSYA’ DITINJAU DARI STRUKTUR KALIMAT BAHASA ARAB SISWA PONDOK PESANTREN HAYATUDDIYAR PEKANBARU - Hauraviesta Rowdiah; Resy Mulyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Arabic holds a strategic position in Islamic education, particularly as the language of the Qur'an and Islamic literature. One essential skill for students to master is *insya’* (Arabic composition writing), which requires not only vocabulary mastery but also the ability to construct sentences according to grammatical rules. *Nahwu* (Arabic syntax), serving as the grammatical foundation of the language, is believed to be closely linked to this skill. However, is this relationship empirically proven within the *pesantren* (Islamic boarding school) environment? This is the central question addressed by this study. The research was conducted at the Hayatuddiyar Islamic Boarding School in Pekanbaru, involving 20 students from grades X and XI as the total sample. A quantitative correlational approach was employed, with data collected through a *nahwu* comprehension test and an *insya’* writing test. The instruments underwent validity and reliability testing, yielding a Cronbach's Alpha value of 0.918, which indicates a very high level of consistency. Following a series of statistical tests including normality (Shapiro-Wilk), linearity, and Spearman Rank correlation it was found that the relationship between *nahwu* comprehension and *insya’* ability is positive and significant, with a correlation coefficient of 0.505 (sig. 0.023 < 0.05). This relationship falls into the moderate category, implying that *nahwu* is not the sole determinant of the quality of students' writing. The coefficient of determination indicates that *nahwu* contributes 34.8%, while the remaining 65.2% is influenced by other factors such as vocabulary mastery, writing habits, and learning motivation. These findings underscore the need to balance *nahwu* instruction with consistent writing practice, ensuring that students not only understand the rules theoretically but are also capable of applying them in actual Arabic language usage.